The Myth of the American Dream and its Ramifications in F. Scott Fitzgerald’s The Great Gatsby - Maafa, Sofiane (LANGUAGE ART, 2021)
The roaring twenties in the United States of America were decisive years for Americans in the transformation their country was about to undergo by the end of the decade. In this article, the researcher will discuss the very definition of the American dream and how the latter was adopted by F. Scott Fitzgerald in his novel The Great Gatsby. The researcher will further explore the failure of the American dream in the novel, mainly depicted in the protagonist Jay Gatsby. This failure was one of other reasons which culminated in the Economic Crash in 1929. In the end, the researcher will discuss how the Economic Crash was a divine punishment to America.